2005
DOI: 10.1016/j.jconrel.2005.06.018
|View full text |Cite
|
Sign up to set email alerts
|

Transcription of plasmid DNA: Influence of plasmid DNA/polyethylenimine complex formation

Abstract: Polyethylenimine (PEI) is one of the most potent non-viral vectors. We have developed a lactosylated PEI (Lac-PEI) to enhance cell-specific transfection and have shown that Lac-PEI is more efficient than unsubstituted PEI for gene transfer into immortalized cystic fibrosis airway epithelial SigmaCFTE29o-cells. As both intact PEI/plasmid and Lac-PEI/plasmid complexes are found in the cell nucleus, we have investigated the transcription efficiency of the plasmid complexed with PEI or Lac-PEI, according to the po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(54 citation statements)
references
References 24 publications
2
50
0
2
Order By: Relevance
“…The highest GFP expression could be detected at N/P ratio 40 as already seen by others (16). It is known that the N/P ratio plays a crucial role for maximization of the transfection efficiency by influencing the size and the charge of the PEI/DNA complexes (17). Therefore, higher N/P ratios increase DNA condensation and endocytotic uptake by the cells (18).…”
Section: Discussionmentioning
confidence: 55%
“…The highest GFP expression could be detected at N/P ratio 40 as already seen by others (16). It is known that the N/P ratio plays a crucial role for maximization of the transfection efficiency by influencing the size and the charge of the PEI/DNA complexes (17). Therefore, higher N/P ratios increase DNA condensation and endocytotic uptake by the cells (18).…”
Section: Discussionmentioning
confidence: 55%
“…Several previous reports comment on a possible influence of the compactness of the polyplex structures on the performance of polyplexes as transfection agents. In particular, the particle size has been shown to affect the internalization pathway whereas compact structures positively influence DNA protection and cytoplasmic transportation [23,27,28]. Figure 5.…”
Section: Influence Of the Transfection Matrixmentioning
confidence: 99%
“…Polyplexes of polymeric gene carriers and pDNA have to be recognized and transcribed after entering the nuclei. It has been reported that polymeric carriers inhibit transcription, and the extent of pDNA condensation may be a major factor determining the transcription efficiency [16]. Since polyplexes are not well transcribed in a cell-free system using reticulocyte lysates due to their strong compaction, it is difficult to quantitatively estimate their transcription efficiencies in living cells.…”
Section: Introductionmentioning
confidence: 99%